Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Solve $(\sqrt{5+2\sqrt{6}})^{x}+(\sqrt{5-2\sqrt{6}})^{x}=10$

I square the both sides and get $(5+2\sqrt{6})^{x}+(5-2\sqrt{6})^{x}=98$. But I don't know how to carry on. Please help. Thank you.

share|cite|improve this question
up vote 16 down vote accepted

Let $t=( \sqrt{5 + 2\sqrt{6}})^{x}\implies (\sqrt{5-2\sqrt{6}})^{x}=\frac{1}{t} $

Thus the equation becomes,

$ t+\frac{1}{t}= 10\implies t^2-10t+1=0$ which is a quadratic equation and have roots $t=5+2\sqrt 6,5-2\sqrt 6$

If $t=5+2\sqrt 6\implies ( \sqrt{5 + 2\sqrt{6}})^{x}=5+2\sqrt 6\implies (5+2\sqrt 6)^{1-x/2}=1\implies 1-x/2=0\implies x=2$

If $t=5-2\sqrt 6 \implies (\sqrt{5+2\sqrt{6}})^{x}=5-2\sqrt 6=\frac{1}{5+2\sqrt 6}\implies (5+2\sqrt 6)^{1+x/2}=1\implies x=-2$

Thus, $x=2,-2$ are the two solutions.


Putting $x=2$ in the original equation gives L.H.S=$5+2\sqrt 6+5-2\sqrt 6=10=$R.H.S

Similarly, putting $x=-2$ also gives L.H.S=$5-2\sqrt 6+5+2\sqrt 6=10=$R.H.S

share|cite|improve this answer
To be perfectly rigorous, you need to check (it's trivial here) that the two possibilities you get are indeed solutions; you only wrote implications ($\Rightarrow$), not equivalences ($\Leftrightarrow$). – Najib Idrissi Sep 25 '12 at 9:39
@nik: i already checked that by putting $x=2$ and $-2$ in the original equation and they both satisfy it. – Aang Sep 25 '12 at 9:41
But you did not write it. – xavierm02 Sep 25 '12 at 13:44
I included it now. – Aang Sep 25 '12 at 13:49
Thank you! I get it now~ – ᴊ ᴀ s ᴏ ɴ Sep 26 '12 at 12:35

Nice solution, just for clarification

$\left(5+2\sqrt{6}\right)^{\frac{x}{2}}\cdot \left(5-2\sqrt{6}\right)^{\frac{x}{2}}=\left[\left(5+2\sqrt{6}\right)\cdot \left(5-2\sqrt{6}\right)\right]^{\frac{x}{2}}=\left[5^2-\left(2\sqrt{6}\right)^2\right]^{\frac{x}{2}}=\left(25-24\right)^{\frac{x}{2}}=1$

and so for $t=\left(\sqrt{5+2\sqrt{6}}\right)^x$......

share|cite|improve this answer
Interesting. Firefox is rendering the first set of brackets as Floor brackets. Checked in IE and it's fine. Also, CTRL + and CTRL - (change font size) renders correctly. – Chris Cudmore Sep 25 '12 at 14:03

Hint $\ $ Put $\rm\ b = 5 + 2\sqrt{6},\,\ a = b^{\,x/2}\ $ in

$$\rm a+ a^{-1} =\, b + b^{-1}\, \Rightarrow\ \{a,a^{-1}\} = \{b,b^{-1}\}\ \ since\ \ (x-a)(x-a^{-1})\, =\, (x-b)(x-b^{-1})$$

Note $\, $ Generally every pair of numbers in a ring is uniquely determined by their sum and product iff the ring is a domain. Above is the special case of this uniqueness result where the product $= 1.\:$ As I often emphasize, uniqueness theorems provide powerful tools for proving equalities.

share|cite|improve this answer
See this duplicate question for further elaboration. – Bill Dubuque Sep 26 '12 at 22:37

Let $t_1=(\sqrt{5+2\sqrt6})^x$, and $t_2=(\sqrt{5-2\sqrt6})^x$.

Now the given equation is:

$$\tag 1 t_1+t_2=10$$


$$\displaylines{ {t_1}\cdot{t_2}&=& {\left( {\sqrt {5 + 2\sqrt 6 } } \right)^x}{\left( {\sqrt {5 - 2\sqrt 6 } } \right)^x} \cr &=& {\left[ {\sqrt {\left( {5 + 2\sqrt 6 } \right)\left( {5 - 2\sqrt 6 } \right)} } \right]^x} \cr &=& {\left[ {\sqrt {{5^2} - {{\left( {2\sqrt 6 } \right)}^2}} } \right]^x} \cr &=& {\left( {\sqrt {25 - 24} } \right)^x} \cr &=& {1^x} = 1 \cr} $$


$$\begin{cases} t_1+t_2=10 \\t_1\cdot t_2=1\end{cases}$$

$\Rightarrow$ $t^2-10t+1=0$

Since $$\frac{1}{{{t_1}}} = {t_2}$$


have $${t_1} + \frac{1}{{{t_1}}} = 10$$ or

$$t_1^2 - 10{t_1} + 1 = 0$$

Note the system is symmetric on the unknowns.

For this quadratic equation we have:


$t_{1,2}=\frac{10\pm 4\sqrt{6}}{2}$

$t_1=5+2\sqrt 6$, $t_2=5-2\sqrt 6$

Now return the inital substition:


$5+2\sqrt 6=(\sqrt{5+2\sqrt6})^x$

$(\sqrt{5+2\sqrt 6})^2=(\sqrt{5+2\sqrt6})^x$ $\Rightarrow$ $x=2$, and

$(\sqrt{5+2\sqrt6})^x=5-2\sqrt 6$

$(\sqrt{5+2\sqrt6})^x=(5+2\sqrt 6)^{-2}$ $\Rightarrow$ $x=-2$

Definitly $x=2$, and $x=-2$ is solve.

share|cite|improve this answer
Please could you tell me the reason why they are negative points – Madrit Zhaku Sep 25 '12 at 19:23

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.